2018
DOI: 10.1016/s0168-8278(18)31335-7
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibody to apolipoprotein A-1 in hepatitis C virus infection: a role in atherosclerosis?

Abstract: Background/purpose One to three per cent of the world's population has hepatitis C virus (HCV) infection, which is not only a major cause of liver disease and cancer but also associated with an increased risk of atherosclerosis, despite an ostensibly favourable lipid profile. Autoantibodies are frequent in HCV infection and emerging evidence shows that autoantibodies could be valuable for cardiovascular disease (CVD) risk stratification. This study investigated a novel independent biomarker of CVD, autoantibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…First of all, these results extend the coverage of virus-mediated anti-apoA-1 IgG induction to SARS-CoV-2, as previously shown for HCV and HIV (26, 27). The inverse associations reported here between anti-apoA-1 IgGs and HDL levels are similar to what has been observed in HCV (26), and are reminiscent of the concept that HCV could hijack the scavenger receptor B-1 (SR-B1)-mediated HDL uptake to infect hepatocytes (26, 43) which has recently been transposed to SARS-CoV-2 by the recent demonstration of Wei and colleagues who identified SR-B1 as an additional receptor facilitating the SARS-CoV-2 entry into cells (44). SR-B1 being the canonical apoA-1/HDL receptor involved in reverse cholesterol efflux and HDL maturation, our results suggest that the molecular mimicry-based anti-apoA-1 IgG response in COVID-19 may concur with other established inflammatory factors to explain the low HDL and apoA-1 levels reported previously in COVID-19 (45, 46).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…First of all, these results extend the coverage of virus-mediated anti-apoA-1 IgG induction to SARS-CoV-2, as previously shown for HCV and HIV (26, 27). The inverse associations reported here between anti-apoA-1 IgGs and HDL levels are similar to what has been observed in HCV (26), and are reminiscent of the concept that HCV could hijack the scavenger receptor B-1 (SR-B1)-mediated HDL uptake to infect hepatocytes (26, 43) which has recently been transposed to SARS-CoV-2 by the recent demonstration of Wei and colleagues who identified SR-B1 as an additional receptor facilitating the SARS-CoV-2 entry into cells (44). SR-B1 being the canonical apoA-1/HDL receptor involved in reverse cholesterol efflux and HDL maturation, our results suggest that the molecular mimicry-based anti-apoA-1 IgG response in COVID-19 may concur with other established inflammatory factors to explain the low HDL and apoA-1 levels reported previously in COVID-19 (45, 46).…”
Section: Discussionsupporting
confidence: 87%
“…To assess the degree of cross reactivity between anti-SARS-CoV-2, anti-apoA-1 IgG (and control IgG) with their respective antigens, delipidated apoA-1 (purified from plasma of healthy blood donors), Spike protein was kindly provided by the institute of technology EPFL (Lausanne, Switzerland), and the two mimic peptides were coated on Maxisorp plates (NuncTM, Roskilde, Denmark) according to the anti-apoA-1 IgG protocol (17, 2126). Commercial polyclonal anti-apoA-1 IgG (Academy Biomedical Company, Houston, TX, USA, ref: 11A-G2) and polyclonal anti-Spike IgG (Thermo Fisher Scientific, Waltham, MA, USA, ref: PA5-81795) with their respective control antibodies: goat IgG (Meridian Life Science, Memphis, TN, USA, ref: A66200H) or rabbit IgG (Dako, Santa Clara, CA, USA, ref: X0903), were added to the coated plate at increasing concentrations (1 to 10 µg/ml) for 1 h. Anti-goat or anti-rabbit alkaline phosphatase-conjugated antibodies (Sigma-Aldrich Chemie GmbH, Buchs, SG, Switzerland, refs: A-7650, A-7539) were added to detect the primary antibody binding.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TLR2 engagement and subsequent activation have been shown to be required for autoantibodies against apoA‐1 (anti‐apoA‐1 IgG) to mediate their pro‐atherogenic effects. 17 , 18 , 19 , 20 Because anti‐apoA‐1 IgGs were shown to represent an independent cardiovascular (CV) risk factor associated with poor prognosis, 21 , 22 , 23 , 24 , 25 , 26 to be elevated after certain viral infections, 27 , 28 and to be preferentially oriented against the c‐ter part of apoA‐1, 29 , 30 we hypothesized that SARS‐CoV‐2 infection could elicit an anti‐apoA‐1 IgG response with substantial overlap with anti‐SARS‐CoV‐2 IgG serology.…”
Section: Introductionmentioning
confidence: 99%
“…Both HCV persistence [30,31] and IFN-α therapy [32] trigger autoimmune reactions resulting in production of auto-antibodies such as ANA, [33] AMA, ASMA and AGPCA [34,7]. In the present study the most reactive autoantibody among Egyptian HCVinfected patients was the ASMA with a recorded prevalence of 69.44% and approximately similar results were obtained by Clifford et al [35] while, others reported that its reactivity ranged between 12-66% based on technical reasons and\or differences in the populations investigated [36].…”
Section: Discussionmentioning
confidence: 99%